Transformasi Pembelajaran Geometri dan Pengukuran melalui Gamifikasi: Meningkatkan Kreativitas, Logika dan Minat Belajar Siswa Sekolah Dasar - Marshanawiah, Andi; Gamar Abdullah; Meylan Saleh; Nurfadliah; Rifda Mardian Arif (Lembaga Pengembangan dan Pengabdian Masyarakat Universitas Muhammadiyah Sorong, 2025)
This community service activity aims to enhance creativity, logic, and student interest in learning at SDN 11 Kota Barat, Gorontalo, through the implementation of gamification in geometry and measurement lessons. Conventional, monotonous teaching methods often result in low student motivation and difficulty in understanding the material, especially in geometry and measurement. Therefore, gamification was chosen as a solution to boost motivation and make learning more engaging and effective. The methods used include teacher training on gamification, development of media based on educational games, and direct implementation in the classroom. Students were involved in games that integrate the concepts of geometry and measurement to enhance their understanding interactively. Evaluations show that the application of gamification successfully increased student interest in learning, strengthened their understanding of the material, and encouraged greater student participation. Additionally, gamification also stimulated creativity and logical thinking in students when solving challenges related to the material. The results of this activity indicate that gamification not only increases student interest and involvement but also improves their understanding of difficult concepts. This activity provides a positive contribution to creating more interactive and enjoyable learning environments and can be applied to improve the quality of education in elementary schools. Keywords: Creativity, Logic, Learning Interest, Gamification, Geometry and Measurement